Camelina variety performance for yield, yield components and oil characteristics - Jewett, Freeborn G., author; Johnson, Jerry J., advisor; Dierig, David, committee member; Jahn, Courtney, committee member (Colorado State University. Libraries, 2013)
Oilseed crops have the potential to increase the stability and sustainability of American agriculture by replacing a portion of the fossil fuels consumed by this sector. There are several candidate oilseed species that have been identified as compatible with a dryland winter wheat-fallow rotation. Of these species, Camelina sativa has been previously identified as being a promising species for the High Plains region. This is due to its short growing season, drought tolerance, cold tolerance and resistance to many of the insect and pest species that cause yield reductions in other Brassica oilseed species. To evaluate the performance of this species in the Western United States, we carried out a two year variety trial in 2011 and 2012 to evaluate the performance of 15 varieties in two distinct geographical regions in the Western United States. Six of the varieties, Ligena, SSD10, SSD177, SSD87, SSD138, and Celine, were in the highest-yielding group of varieties in all of our combinations of environments, including irrigated environments. Five of the varieties have been identified as containing favorable alleles for yield and drought tolerance. These SSD varieties yielded well in our study but did not significantly outperform their parental varieties across all environments. The mean yield for the trial across all environments was 813 kg ha-1. Lower-latitude environments in Colorado and Wyoming were not as high-yielding as higher-latitude environments in Montana and Washington State. Camelina did not perform as well at low latitudes even under irrigated conditions during the two years of our study. The low yields can be attributed to above-average, high temperatures. Decreasing the average maximum temperature during the growing season resulted in increased yield and was positively correlated with an increase in the percent oil and percent of the oil profile comprised of polyunsaturated fatty acid and a decrease in the percent oil comprised of saturated fatty acids. From an agronomic perspective, the focus might be on reducing the number of warm days so that they comprise no more than 17% of the growing season. In addition to yield, this study looked at the components of yield to see how they were affected by environmental conditions and how they contributed to yield. The number of plants per hectare had the largest effect on yield. This yield component showed significant genotype by environment (GxE) interaction. This yield component is strongly influenced by environmental conditions and not genotype. This suggests that the quickest and easiest way to increase yield is to increase the planting density of the field. In a dryland agricultural system, increased density may have a negative tradeoff in the form of increased water usage of the crop. If breeders are interested in choosing a variety for seed yield improvement, it would be beneficial to choose thousand seed weight, as this is highly heritable and related to genotype. The number of pods per plant has little relationship with the overall yields for camelina and showed significant GxE interaction. In addition to the variety trial, we assessed the fall planting potential of 11 winter lines and three spring lines of camelina in Fort Collins, CO and Rocky Ford, CO from 2010 to 2011. We found significant differences between the dates of planting (p <0.001). The average yield of the fall seeded entries was 434 kg ha-1, which was less than the average yield of 1033 kg ha-1 for a nearby spring seeded camelina variety trial. This showed that through fall seeding of camelina, it is possible to get a stand, but the yields are lower than spring seeded camelina. Our trial included an entry of pennycress (Thlaspi arvense), another oilseed species with potential for Colorado agricultural areas. This preliminary trial in 2010 to 2011 found that under irrigation, pennycress yielded 1392 kg ha-1, which was much higher than the fall seeded camelina. In a follow up trial of the dryland potential of four lines of pennycress in Akron, CO in 2012, excessive drought conditions resulted in a failure of the plots.
Keywords: biofuels; lipid; genotype x environment